Research on dynamics and failure mechanism of herringbone planetary gearbox in wind turbine under gear surface pitting. (April 2023) - Wang, Siyu; Zhu, Rupeng
Highlights: Gear tooth surface pitting is modelled as Gaussian distribution and random distribution. A mesh stiffness calculation model of helical gear pair with tooth pitting is proposed. The effect of tooth pitting aggravation and position on the mesh stiffness is investigated. The vibration-based fault diagnosis for planetary gearbox under tooth pitting is conducted. The experimental test is conducted to validate the accuracy of the theoretical results. Abstract: In this paper, the herringbone planetary gear system in wind turbine gearbox with tooth surface pitting is modelled, and the time-varying mesh stiffnesses of the gear meshing pairs are calculated. The results show that the aggravation of tooth surface pitting weakened the mesh stiffnesses in different levels based on the pitting condition. Based on the dynamic model of the transmission system, the vibration signal model of the gearbox is established, considering the vibration transmission path and attenuation. The gearbox vibration acceleration signals under tooth surface pitting in different conditions are simulated, the obtained time-domain signals reveal abnormal fluctuations, and the frequency-domain signals illustrate abundant sidebands near harmonics of meshing frequency and low frequency area. For different pitting conditions, the fault frequencies vary, the results provide theoretical basis for the fault analysis and diagnosis of the gearbox. Furthermore, the theoretical analysis results are validated against experimental test results based on the test bench of herringbone planetary gearbox with tooth surface pitting in sun gear.